Preserved C-peptide is common and associated with higher time in range in Chinese type 1 diabetes - Liu, Wei; Fang, Yayu; Cai, Xiaoling; Zhu, Yu; Zhang, Mingxia; Han, Xueyao; Li, Juan; Yin, Sai; Cai, Deheng; Chen, Jing; Wang, Lei; Shi, Dawei; et al. (Frontiers in Endocrinology, 2024)
Objective The aim of this study is to determine the residual C-peptide level and to explore the clinical significance of preserved C-peptide secretion in glycemic control in Chinese individuals with type 1 diabetes (T1D). Research design and methods A total of 534 participants with T1D were enrolled and divided into two groups, low–C-peptide group (fasting C-peptide ≤10 pmol/L) and preserved–C-peptide group (fasting C-peptide >10 pmol/L), and clinical factors were compared between the two groups. In 174 participants who were followed, factors associated with C-peptide loss were also identified by Cox regression. In addition, glucose metrics derived from intermittently scanned continuous glucose monitoring were compared between individuals with low C-peptide and those with preserved C-peptide in 178 participants. Results The lack of preserved C-peptide was associated with longer diabetes duration, glutamic acid decarboxylase autoantibody, and higher daily insulin doses, after adjustment {OR, 1.10 [interquartile range (IQR), 1.06–1.14]; OR, 0.46 (IQR, 0.27–0.77); OR, 1.04 (IQR, 1.02–1.06)}. In the longitudinal analysis, the percentages of individuals with preserved C-peptide were 71.4%, 56.8%, 71.7%, 62.5%, and 22.2% over 5 years of follow-up. Preserved C-peptide was also associated with higher time in range after adjustment of diabetes duration [62.4 (IQR, 47.3–76.6) vs. 50.3 (IQR, 36.2–63.0) %, adjusted P = 0.003]. Conclusions Our results indicate that a high proportion of Chinese patients with T1D had preserved C-peptide secretion. Meanwhile, residual C-peptide was associated with favorable glycemic control, suggesting the importance of research on adjunctive therapy to maintain β-cell function in T1D.